Origin and evolution of silicic magmas in oceanic arcs: an in situ study from St Lucia, Lesser Antilles - Bezard, Rachel; Turner, Simon P.; Schmitt, Axel Karl; Lindsay, Jan Marie (Journal of petrology, 2017)
Processes linked with the genesis, evolution and emplacement of silicic complexes in arcs are still poorly constrained. Of particular interest are the depth of magma production, the relative contribution of crystal fractionation versus crustal partial melting and the timescales involved. The Soufrière Volcanic Complex (SVC) on St Lucia is one of the largest silicic centres in the Lesser Antilles arc. Here we present the results of a detailed mineralogical study, including in situ Sr isotopes in plagioclase and in situ δ18O in dated zircons, of both SVC and Pre-SVC volcanic rocks to place constraints on the processes intrinsic to the development and evolution of the silicic complex. These data suggest that the production of silicic magma in the SVC occurs in two stages. The first stage involves differentiation of mafic magma by crustal assimilation and mineral fractionation in the middle-lower crust of the arc to produce magmas with intermediate compositions. These intermediate magmas are water-rich (∼7 wt %) and have high 87Sr/86Sr, Ba, Sr and La/Sm (∼5) compared with Pre-SVC lavas. Near-constant trace element and isotopic compositions throughout the SVC lifespan indicate that the same process was persistent over the last 600 kyr. In the second stage, the intermediate magmas are transferred to a shallower and more differentiated chamber (∼6 km depth). During ascent, any crystals or xenocrysts residual from stage one in the deeper chamber become fully resorbed and the magma crystallizes calcic amphibole microphenocrysts, followed by anorthite-rich plagioclase close to or at the water saturation depth. During mixing upon recharge within the shallow chamber, anorthite-rich plagioclase from the recharging magma is partially resorbed; so are the crystals in equilibrium with the resident differentiated magma. The recharge event probably causes chamber-wide convection. Mixing is thought to trigger eruption of the silicic complex magmas.
Gesehen am 21.02.2018